Mice with lung airway ciliopathy develop persistent Mycobacterium abscessus lung infection and have a proinflammatory lung phenotype associated with decreased T regulatory cells - Nava, Audrey; Hahn, Andrew C.; Wu, Terry H.; Byrd, Thomas F. (Frontiers in Immunology, 2022)
Human pulmonary infection with non-tuberculous mycobacteria (NTM) such as Mycobacterium abscessus (Mabs) and Mycobacterium avium complex (MAC) occurs in seemingly immunocompetent patients with underlying structural lung disease such as bronchiectasis. We have used a mouse strain containing a conditional floxed allele of the gene IFT88, which encodes for the protein Polaris. Deletion of this gene in adult mice reportedly leads to loss of cilia on lung airway epithelium and development of bronchiectasis. Using this model, we show that Mabs persists in the lungs of mice with lung airway ciliopathy compared to control mice. As assessed by T lymphocyte and cytokine analysis, mice deficient in lung cilia develop an immunologic lung phenotype characterized by increased levels of proinflammatory cytokines and a relative percent decrease in pulmonary CD4+FoxP3+ T lymphocytes compared to control mice. These results indicate that Th17/Treg imbalance may contribute to Mabs persistence in the lungs of mice with lung airway ciliopathy.